RELIGIOSITY DOES NOT MODERATE THE RELATIONSHIP BETWEEN FORGIVENESS AND MENTAL HEALTH OF SURVIVORS OF THE 2004 TSUNAMI INDONESIA: A CROSS-SECTIONAL STUDY - Priya Exsa; Zaujatul Amna; Dahlia; Muhamad Antos Riady (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2026)
Background: The tsunami that struck Aceh in 2004 had widespread negative impacts, including material losses, physical health problems, and psychological stress experienced by survivors. Twenty years after the event, various mental disorders such as anxiety, depression, and other emotional disorders are still found among the affected communities. In the religious culture of Aceh, religiosity is seen as a form of coping that can aid in psychological recovery. Purpose: This study aims to examine the role of religiosity as a moderate variable in the relationship between forgiveness and mental health among Aceh tsunami survivors. Method: The study used a quantitative approach with multiple regression analysis technique, involving 464 survivors selected through purposive sampling. Participants completed three research instruments, namely the Mental Health Inventory-18, Heartland Forgiveness Scale, and The Centrality of Religiosity Scale. Results: Data analysis used Hayes PROCESS moderation model 1, which showed that religiosity did not act as a moderator variable in the relationship between forgiveness and mental health. Moreover, no significant direct relationship was found between forgiveness and mental health. Conclusion: These findings indicate that forgiveness does not directly influence the level of mental health among tsunami survivors, and that religiosity does not strengthen this relationship in this context. Abstrak Latar Belakang: Tsunami Aceh 2004 menimbulkan dampak negatif luas, termasuk kerugian materiil, gangguan kesehatan fisik, dan tekanan psikologis pada penyintas. Dua puluh tahun setelah kejadian, gangguan mental seperti kecemasan, depresi, dan gangguan emosi masih ditemukan di masyarakat terdampak. Dalam budaya Aceh yang religius, religiusitas dipandang sebagai bentuk koping yang dapat membantu pemulihan psikologis. Tujuan: Penelitian ini menguji peran religiusitas sebagai variabel moderator dalam hubungan antara pemaafan dan kesehatan mental pada penyintas tsunami Aceh. Metode: Penelitian menggunakan pendekatan kuantitatif dengan analisis regresi linier berganda, melibatkan 464 penyintas yang dipilih melalui purposive sampling. Partisipan mengisi tiga instrumen: Mental Health Inventory-18, Heartland Forgiveness Scale, dan The Centrality of Religiosity Scale. Hasil: Analisis data menggunakan model moderasi PROCESS Hayes model 1 menunjukkan religiusitas tidak berperan sebagai variabel moderator dalam hubungan antara pemaafan dan kesehatan mental. Tidak ditemukan hubungan langsung signifikan antara pemaafan dan kesehatan mental. Kesimpulan: Temuan ini menunjukkan pemaafan tidak secara langsung memengaruhi kesehatan mental penyintas tsunami, dan religiusitas tidak memperkuat hubungan tersebut.